PEMIKIRAN PENDIDIKAN AHMAD DAHLAN DALAM PENGUATAN PENDIDIKAN KARAKTER DI ERA KURIKULUM MERDEKA - Vionita (JURNAL EKSPERIMENTAL : Media Ilmiah Pendidikan, 2025)
Education plays a strategic role in shaping the character of a nation. However, the era of globalization presents challenges such as moral degradation and the erosion of national values, making the strengthening of character education an urgent necessity. The government has responded by implementing the Merdeka Curriculum, which emphasizes flexible learning and character development through the Pancasila Student Profile. This article examines the relevance of K.H. Ahmad Dahlan’s educational thought in reinforcing character education within the context of the Merdeka Curriculum using a library research method. The findings indicate that Ahmad Dahlan’s concept—emphasizing the integration of faith, knowledge, action, and morality—aligns with the six dimensions of the Pancasila Student Profile and supports the implementation of the Pancasila Student Profile Strengthening Project (P5). Therefore, his educational philosophy remains relevant as a foundation for strengthening character education in Indonesia’s contemporary education system.